Kierunki zaangażowania Jana Korneckiego w prace zjednoczeniowe polskich towarzystw oświatowych w latach 1923-1935 - Michalski, Grzegorz (Studia Edukacyjne, 2018)
After Poland regained independence in 1918, educational societies played an important role in the education of the society. Jan Kornecki was one of many community workers who continued activities in that area started during the times of national bondage. On behalf of the Polish Educational Society in Warsaw [Polska Macierz Szkolna], he became a member of a pioneer group trying to unify the actions and strengthen the cooperation between educational societies in various districts of Poland. After the establishment of the Liaison Commission of Polish Educational Societies [Komisja Porozumiewawcza Polskich Towarzystw Oświatowych], he accepted the position of the secretary of the Commission’s Executive Department and was responsible for initiating and maintaining permanent contacts between the societies forming the Commission. Apart from maintaining ongoing relationships with community workers in the places of their local activities, he prepared the First Polish Educational Congress, which was convened in December 1924 in Warsaw. J. Kornecki rendered great services in founding a new educational organization named The Union of Polish Educational Societies [Zjednoczenie Polskich Towarzystw Oświatowych], which was established in 1927 based on the experiences gathered by the Liaison Commission, which operated earlieroku He took the function of the manager of the Union’s Executive Department Office; his responsibilities included delegating and supervising tasks performed by clerks employed in the Office, managing the property and funds, and drawing up reports of activities. He moreover organized and convened annual and extraordinary meetings of delegates and implemented the resolutions adopted, prepared plans and programmes of quarterly off-schedule meetings of the Executive Department, represented the Union during external relations, mainly with state and local government institutions and first of all initiated and maintained regular relationships with separate associations and provided them with all kinds of aid, e.g. by organizing annual conferences for educational managers.